The reward of unification: A realist reading of the predictive processing theory. (January 2018) - Beni, Majid Davoody
Abstract: In a recent paper, Colombo and Wright (C & W for short) built on their neat assessment of the activity of mesocorticolimbic dopaminergic (DA) systems to argue that hierarchical predictive processing theory of the brain (PTB) is not the grand unifying theory that has been claimed by its advocates. To the contrary, they argued that the scientific practice is consistent with a pluralist reading (Colombo & Wright, 2016). Despite its reliance on solid experimental resources, C & W's defence of explanatory pluralism is adorned with sophisticated philosophical assumptions. Of course, this provides all the more reason to admire C & W's enterprise on account of its tasteful combination of scientific and philosophical insights. However, despite being conscious about the relation of their works to the philosophy of science, C & W have presented their pluralistic construal as if it is a direct consequence of the scientific status quo. This paper aims to defend a unificationist account. C & W's endeavour might successfully block the way of some discredited forms of unificationism (such as micro-reductionism and Nagelian model). However, in this paper, I argue that it fails to establish its pluralist reading in the face of the more advanced forms of unificationism that are at issue in the contemporary philosophy of science (mechanistic accounts or structural realist accounts). After introducing these more sophisticated theories of unification schematically, I refer to the scientific practice to show how the free-energy formulation of PTB (as well as a case that has been mentioned by C & W as evidence for pluralistic reading) could be construed along the lines of unificationism. I end the paper with reminding that the reward of unification is realism.